Object Damage Risk Evaluation in the European Project Climate for Culture. (November 2015) - Huijbregts, Zara; Schellen, Henk; Martens, Marco; van Schijndel, Jos
Abstract: In the European project Climate for Culture we evaluated the risks for valuable historical objects exposed to changing indoor conditions due to external climate change. For some well-defined objects, like wooden paintings, experiments and computer simulations have led to descriptions of safe boundary conditions to prevent various types of damage such as mechanical damages. Within the Climate for Culture project, we have investigated whether the results from literature can be used to construct so-called damage functions to evaluate the risks for objects in future. Furthermore, we have tried to evaluate if such damage functions can be used to evaluate the risks that these objects were exposed to in the past, present and future. Within Building Physics, computer simulation models have been developed to calculate the expected indoor climate of buildings exposed to a varying outdoor climate. This outdoor climate might be constructed from a historical data file (more than 100 years ago), the present (less than 50 year ago) or predicted future data from outdoor climate prediction computer models (for the next 100 years). The simulated indoor climate will create the input for the risk evaluation. The input is coupled to damage functions to directly predict the risks for damage to objects. This paper will deal with the modelling approach and will show the potential for damage risk evaluation. The historic, present and future indoor climate conditions in a characteristic historic building have been modelled and the damage risk to historical objects has been compared when the building is virtually placed on 468 different locations throughout Europe. In this way, the impact of future climate change on the indoor climate conditions in a building and damage potential to its collection can be assessed for areas all over Europe.